The Influence of Quality of Financial Statements of Waqf Institutions on Stakeholder Trust - Wali Saputra; Bakri Bakri (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
This study aims to analyze the effect of the quality of the financial statements of waqf institutions in Riau on stakeholder trust. This study used primary data obtained by distributing questionnaires to 157 stakeholders who always interact with waqf institutions. Data analysis methods used in this study include research instrument and hypothesis testing using regression analysis. The results of the study show that the quality of the waqf institution's financial statements has an effect on stakeholder trust. This is based on the calculated t value of 5.851 with a significance level of 0.000 (<0.05) and t table 1.972141. This shows that t count is greater than t table (5.851 > 1.972141). The results of this study concluded that the quality of the waqf institution's financial statements affects stakeholder trust